2013
DOI: 10.1002/chem.201204313
|View full text |Cite
|
Sign up to set email alerts
|

A New Route for the Prebiotic Synthesis of Nucleobases and Hydantoins in Water/Ice Solutions Involving the Photochemistry of Acetylene

Abstract: The origin of nucleobases and other heterocycles is a classic question in the chemistry of the origins of life. The construction of laboratory models for the abiotic synthesis of nitrogen heterocycles in plausible natural conditions also aids the understanding and prediction of chemical species in the Solar System. Here, we report a new explanation for the origin of hydantoins, purines, and pyrimidines in eutectic water/ice/urea solutions driven by ultraviolet irradiation (in the 185-254 nm range, UVC) of acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 77 publications
1
76
1
4
Order By: Relevance
“…The green arrows show a plausible prebiotic pathway, experimentally proven by Butch et al., which provides a feedstock for entry into rTCAC. The violet arrows indicate the relationship proposed by Menor‐Salván and Marín‐Yaseli . The orange arrows show the pathway proposed by Guzman and Martin to enter rTCAC based on the catalytic properties of ZnS surfaces .…”
Section: Resultsmentioning
confidence: 91%
“…The green arrows show a plausible prebiotic pathway, experimentally proven by Butch et al., which provides a feedstock for entry into rTCAC. The violet arrows indicate the relationship proposed by Menor‐Salván and Marín‐Yaseli . The orange arrows show the pathway proposed by Guzman and Martin to enter rTCAC based on the catalytic properties of ZnS surfaces .…”
Section: Resultsmentioning
confidence: 91%
“…[12] Notwithstanding the central role of 1,i ts formation in interstellar environments has remained elusive.Its structure is C s symmetric and displays two conformers:( E,Z)a nd the thermodynamically preferred (E,E)c onformation. [14] Recently, 1 was identified in the polymerization of hydrogen cyanide in aqueous solution as proposed by Eschenmoser. [13] Theprebiotic origin of 1 has remained elusive, and Eschenmoser concluded that hitherto unknown reservoirs of 1 must exist as am ajor prerequisite for the "glyoxylate scenario".…”
Section: Dedicated To Drhans Peter Reisenauermentioning
confidence: 99%
“…Alternative chemical pathways toward the formation of amino acids in photolyzed ice mixtures have also been recently proposed (Bossa et al 2010) with circularly polarized light initiating an enantiomeric excess of amino acids (Modica et al 2014). Various nucleobases synthesis pathways have been established since the 1960s (see for instance : Ferris and Orgel 1966;Menor-Salván and Marín-Yaseli 2013;Miyakawa et al 2002aMiyakawa et al , 2002bMiyakawa et al , 2002cOro 1960;Oro and Kimball 1961;Robertson and Miller 1995) (see also Martins 2012 for a review). It has also been shown that a component of the organic residue synthesized by irradiation of interstellar and cometary ice spontaneously organizes into boundary structures .…”
Section: Classical Approachmentioning
confidence: 99%